Anti-Cancer Nanomedicines: A Revolution of Tumor Immunotherapy - Li, Wei; Peng, Anghui; Wu, Huajun; Quan, Yingyao; Li, Yong; Lu, Ligong; Cui, Min (Frontiers in Immunology, 2020)
Immunotherapies have been accelerating the development of anti-cancer clinical treatment, but its low objective responses and severe off-target immune-related adverse events (irAEs) limit the range of application. Strategies to remove these obstacles primarily focus on the combination of different therapies and the exploitation of new immunotherapeutic agents. Nanomedicine potentiates the effects of activating immune cells selectively and reversing tumor induced immune deficiency microenvironment through multiple mechanisms. In the last decade, a variety of nano-enabled tumor immunotherapies was under clinical investigation. As time goes by, the advantages of nanomedicine are increasingly prominent. With the continuous development of nanotechnology, nanomedicine will offer more distinctive perspectives in imaging diagnosis and treatment of tumors. In this Review, we wish to provide an overview of tumor immunotherapy and the mechanisms of nanomaterials that aim to enhance the efficacy of tumor immunotherapy under development or in clinic treatment.